Ageing exacerbates damage of systemic and salivary neutrophils from patients presenting Candida-related denture stomatitis - Gasparoto, Thaís Helena (BioMed Central, 2009)
BACKGROUND: Ageing leads to a decline in the function of the immune system, increasing the body's susceptibility to infections through the impairment of T-cells, macrophages, neutrophils and dendritic cells Denture stomatitis is a primary oral disease affecting elderly denture wearers. The major etiologic factor involved in this pathology is the infection by Candida albicans, an opportunistic pathogen that causes local and disseminated diseases in immunosuppressed humans. Neutrophils play a critical role in the immune response against C. albicans and are continually present in the salivary fluid and in the blood. The aim of this study was to determine ageing-related changes in salivary and blood neutrophils and their potential implications in Candida-related denture stomatitis. RESULTS: Our results showed a lower number of neutrophils in the saliva from patients presenting Candida-related denture stomatitis in comparison to their matched controls. Furthermore, fewer neutrophils were isolated from the saliva of aged control individuals in comparison to matched younger subjects. CXCR1, CD62L and CD11b expression were significantly greater on systemic neutrophils from younger control individuals. Elderly individuals showed more apoptotic salivary neutrophils and lower GM-CSF levels than younger ones, regardless of the occurrence of Candida infection. On the other hand, CXCL-8 concentrations were higher in the saliva from elderly individuals. Besides, TNF-α was detected at elevated levels in the saliva from infected elderly subjects. Salivary neutrophils from elderly and young patients presented impaired phagocytic activity against C. albicans. However, just systemic neutrophils from elderly showed decreased phagocytosis when compared to the younger ones, regardless of the occurrence of infection. In addition, neutrophils from aged individuals and young patients presented low fungicidal activity. CONCLUSION: The data suggests that the Candida related-denture stomatitis is associated to neutrophils function deficiency, and ageing drastically appears to alter important characteristics of such cells, facilitating the establishment of this infection.